TPACK on differentiated instruction: Students' critical listening literacy skills - Naryatmojo, Deby Luriawati; Baehaqie, Imam; Hasyim, Mohamad Yusuf Ahmad; Cahyo, Ahmad Nur; Azam, Muhammad (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2026)
The integration of Technological, Pedagogical, and Content Knowledge (TPACK) has been widely advocated in technology-enhanced learning; however, empirical evidence linking TPACK-based differentiated instruction to the development of critical listening literacy in higher education remains limited. This study addresses this gap by examining the pedagogical impact of a TPACK-integrated differentiated instructional model on undergraduate students' literal and critical listening competencies. A quasi-experimental non-equivalent control group design was employed involving 72 students from two Indonesian public universities. The experimental group (n = 37) received TPACK-based differentiated instruction, while the control group (n = 35) underwent conventional teaching. Data were analyzed using parametric statistical procedures, including paired- and independent-sample t-tests and normalized gain (N-gain) analysis. Results demonstrate statistically significant improvements in both groups; however, the experimental group achieved substantially greater learning gains (M_pre = 73; M_post = 87) compared to the control group (M_pre = 69; M_post = 80), with a high N-gain score (0.53) versus a moderate gain (0.35). The findings suggest that systematic integration of technological, pedagogical, and content knowledge within differentiated frameworks enhances higher-order listening literacy by promoting cognitive engagement and evaluative processing. This study contributes empirical support to the TPACK framework by extending its application to critical literacy development and offers pedagogical implications for technology-mediated language instruction in higher education contexts.